Repositioning of the β-Blocker Carvedilol as a Novel Autophagy Inducer That Inhibits the NLRP3 Inflammasome - Wong, Wei-Ting; Li, Lan-Hui; Rao, Yerra Koteswara; Yang, Shih-Ping; Cheng, Shu-Meng; Lin, Wen-Yu; Cheng, Cheng-Chung; Chen, Ann; Hua, Kuo-Feng (Frontiers in Immunology, 2018)
The NLRP3 inflammasome is a multiprotein complex that plays a key role in the innate immune system, and aberrant activation of this complex is involved in the pathogenesis of inflammatory diseases. Carvedilol (CVL) is an α-, β-blocker used to treat high blood pressure and congestive heart failure; however, some benefits beyond decreased blood pressure were observed clinically, suggesting the potential anti-inflammatory activity of CVL. In this report, the inhibitory potential of CVL towards the NLRP3 inflammasome and the possible underlying molecular mechanisms were studied. Our results showed that CVL attenuated NLRP3 inflammasome activation and pyroptosis in mouse macrophages, without affecting activation of the AIM2, NLRC4 and non-canonical inflammasomes. Mechanistic analysis revealed that CVL prevented lysosomal and mitochondrial damage and reduced ASC oligomerization. Additionally, CVL caused autophagic induction through a Sirt1-dependent pathway, which inhibited the NLRP3 inflammasome. In the in vivo mouse model of NLRP3-associated peritonitis, oral administration of CVL reduced (1) peritoneal recruitment of neutrophils; (2) the levels of IL-1β, IL-18, active caspase-1, ASC, IL-6, TNF-α, MCP-1 and CXCL1 in the lavage ﬂuids; and (3) the levels of NLRP3 and HO-1 in the peritoneal cells. Our results indicated that CVL is a novel autophagy inducer that inhibits the NLRP3 inflammasome and can be repositioned for ameliorating NLRP3-associated complications.